Risk Factors for Impaired Outcomes After Surgery in Patients With Spontaneous Intracerebral Hemorrhage - Sivavetpikul, Peerut (Health Science Clinical Research, 2025)
Objective: To investigate prognostic factors for mortality and morbidity in patients with hemorrhagic stroke who underwent surgical treatment at Phichit Hospital. Methods: This prognostic study was conducted as a retrospective cohort of patients aged over 18 years who underwent surgical treatment for intracerebral hemorrhage at Phichit Hospital between October 1, 2020, and May 31, 2024. Prognostic factors were analyzed using logistic regression. Results: A total of 201 patients were included. The overall mortality rate was 29.9%. Among survivors, the morbidity rate was as high as 86.52%. Factors significantly associated with mortality included low initial level of consciousness (Glasgow Coma Scale, GCS ≤5), coagulopathy, warfarin use, comorbidities (chronic kidney disease/atrial fibrillation), and postoperative complications such as sepsis and acute kidney injury (AKI). Factors associated with morbidity included age over 60 years, hematoma volume ≥30 mL, dyslipidemia, and postoperative infections (pneumonia and urinary tract infection). Conclusions: Early identification and close monitoring of high risk patients such as those with impaired consciousness, coagulopathy, or major comorbidities together with strict prevention of postoperative infections, are crucial strategies to reduce mortality and improve patient outcomes. These prognostic factors may also serve as valuable information for providing prognostic counseling to patients’ families before and after surgery.